Organizational trauma – Types of organizational forgetting in the case of Belgrade theaters - Milena Dragićević-Šešić (University of Belgrade, 2017)
Organizational memory studies (OMS) frame memory in a managerial mode, treating it as a data storage, limiting the scope from wider field of social memory studies. There is a lack of understanding about how the process of institutional forgetting works and how some memories stay a part of oral narratives and communicative social memory while they are omitted from the official memory represented by the official documents and events of remembering. Inspired by Paul Connerton’s article on the typology of forgetting we explore his typology in selected case studies of three public theaters located in Belgrade, focusing on remembering policy and practices investigating if a type of forgetting typical for a state/society/nation level is possible to be applied in the context of a cultural organization. We agree with Wessel and Moulds that developing common language and terminology would be important and beneficial for cross disciplinary dialogue. In this sense, the study shows how the typology of forgetting in societies can be applied and developed in the organizational memory studies and cultural management. The focus of the research is the dynamics of remembering and forgetting explored through analysis of the interaction between changing context, official institutional memories, and social communicative memories.